Setting the Lipid Component of the Diet: A Work in Process–. Issue 1 (11th January 2017) - Del Razo Olvera, Fabiola M; Melgarejo Hernández, Marco A; Mehta, Roopa; Aguilar Salinas, Carlos A
Abstract: Some of the most relevant yet controversial issues in nutrition are those surrounding the guidelines on quality and quantity of dietary fat in the prevention and treatment of cardiovascular diseases and coronary heart diseases. Conflicting evidence questions the credibility of the previous dietary guidelines, particularly the quality of the evidence on which these recommendations were based. It is therefore important to explore the changes that have occurred in these guidelines and their influence on the adoption of different dietary patterns over time. In this review, we summarize the evolution of the fat component of the dietary guidelines, discuss controversial aspects, and highlight the areas in which additional evidence is still needed. Over the years, the scientific community has shown an obsession for calories in a diet instead of focusing on the quality of the food that makes up the diet. This is why certain authors have identified the importance of evaluating a diet focusing on diet patterns, rather than single isolated nutrients. This approach has been proposed in the most recent Dietary Guidelines for Americans.